"Párhuzamos életrajzok" a Magyar Anjou Legendárium Márton- és Gellért-ciklusa - Szakács Béla Zsolt (Szegedi vallási néprajzi könyvtár, 2001)
We have more than a thousand manuscripts of the great hagiographical collection, the Legenda Aurea of Jacobus de Voragine from the 13th century, but there is only one codex which not only illustrated the text but translated it into a language of images. It is related to the Hungarian Anjous, that is why the codex is titled 'Hungarian Angevin Legendary'. The pages of the codex are spread over different collections of the world. Nowadays 58 legends are known on 142 pages, altogether 549 images. Some more important legends, as that of the apostles or the Anjous' favourite saint, King Ladislas, occupy 20-24 images. The paper try to demonstrate in two exam ples, St. M artin and St. Gerard, how these cycles were orgenised. Two pictures of the supposed eight are emphasising the role of Martin as a bishop. Five images show the miracles of the saint and only one is dedicated to the charity of St. Martin, to the event wich is his most popular story. Martin is the symbolic saint who gives half his goods to the poor. This scene is the most frequently represented in medieval art. In the Hungarian Angevin Legendary his miraculous actitvity is much more emphasized which is correlated with the written legend. The legend of St. Gerard is preserved completely in the Legendary. The first picture represents the saint discussing with King St. Stephen. On the second image the saint is represented as a hermit in Bakonybél with a book in his hand. The third one depicts the consecration of St. Gerard to the bishop of Csanád, on the next picture he is preaching to the people. The following pictures show his martyrdom and burial. It can be supposed that the painter(s) of the Hungarian Angevin Legendary could not use any iconographical tradition working on the cycle of St. Gerard.